An Empirical Investigation of Corporate Citizenship in Australia and Turkey - Küskü, Fatma; Zarkada, Anna K. (My University, 2004)
This paper describes a study of corporate citizenship practices and its relationship to dimensions of internal and external corporate culture, customer loyalty and organizational commitment. Empirical data was collected from a cross-industry sample in Turkey and Australia using a questionnaire form developed and validated for other cultures. It was shown that Australian and Turkish firms' practices differed significantly on a number of important variables, but also that it is possible to compare corporate citizenship practices in a way that is not culture-specific.
Keywords: Corporate citizenship; Quantitative approaches; Corporate culture